First argiolestid damselfly (Odonata: Zygoptera) from the late Palaeocene of Northwest Argentina - Petrulevicius, Julian Fernando (2020)
Megapodagrionids in the wide sense are a polyphyletic group of damselflies (Huang et al., 2018). In recent studies there is a tendency to restrict the Megapodagrionidae only to few genera, and to over rank some subfamilies such as Philosininae and Argiolestinae to family level (Kalkman & Theischinger, 2013; Dijkstra et al., 2014). These efforts are based on nymphal (Kalkman et al., 2010) and wing characters (Kalkman & Theischinger, 2013).